2013
DOI: 10.1016/j.imbio.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to substrates induces dendritic cell endothelization and decreases immunological response

Abstract: Dendritic cells (DCs) are antigen presenting cells capable of inducing specific immune responses against microbial infections, transplant antigens, or tumors. DCs have been shown to possess a high plasticity showing different phenotypes in response to their microenvironment. For example, tumor-associated DCs can acquire an angiogenic phenotype thus promoting tumor growth. Further, DCs cultured in vitro under different conditions are able to upregulate the expression of endothelial markers and to express angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In some kinds of solid tumors, angiopoietins were reported to be associated with immune cells including TAMs, NK cells and neutrophils, but whether it effects in a similar way in the glioma microenvironment requires further confirmation ( 164 , 165 ). Available evidences showed that Tie2 was expressed in immunocytes including DCs, TAMs, T lymphocytes, neutrophils and mast cells, combining with the findings that ANG2 was expressed aberrantly in gliomas, provide us a feasible theoretical basis for further studying the ANG and immune cell interactions in the glioma microenvironment ( 62 , 166 169 ).…”
Section: Angiopoietinsmentioning
confidence: 97%
See 1 more Smart Citation
“…In some kinds of solid tumors, angiopoietins were reported to be associated with immune cells including TAMs, NK cells and neutrophils, but whether it effects in a similar way in the glioma microenvironment requires further confirmation ( 164 , 165 ). Available evidences showed that Tie2 was expressed in immunocytes including DCs, TAMs, T lymphocytes, neutrophils and mast cells, combining with the findings that ANG2 was expressed aberrantly in gliomas, provide us a feasible theoretical basis for further studying the ANG and immune cell interactions in the glioma microenvironment ( 62 , 166 169 ).…”
Section: Angiopoietinsmentioning
confidence: 97%
“…This effect was ascribed to the CCL21-dependent CD8+ T cell activation and DC trafficking ( 61 ). Tumor-associated dendritic cells (TA-DCs) suppress anti-tumor immune responses, but when treated with inflammatory molecules, TA-DCs gain the ability to reactivate T cells ( 62 ).…”
Section: Vegfmentioning
confidence: 99%
“…Upon treatment, the cells regain their ability to activate antigen-specific T cells (10, 49, 50). Considering that cancer-associated DCs can harbor tumor antigen, a compelling strategy would be to reprogram them in vivo .…”
Section: Reprograming Cancer-associated DC To Induce Anti-tumor Immunitymentioning
confidence: 99%
“…The “immune paralysis” of cancer-associated DCs can be overcome in an experimental setting by blocking IL-10R while simultaneously activating specific pattern recognition receptors (PRRs). Upon treatment, the cells regain their ability to activate antigen-specific T cells ( 10 , 49 , 50 ). Considering that cancer-associated DCs can harbor tumor antigen, a compelling strategy would be to reprogram them in vivo .…”
Section: Reprograming Cancer-associated DC To Induce Anti-tumor Immunmentioning
confidence: 99%
“…A modulation of the host defence into immune settings, supporting or not cancer cell survival, is assumed as one of the most important conditions governing the extend of tumour growth and spreading [66,67]. Numerous tumour specific and tissue damage associated humoral factors attract immune cells and modulate their functional properties [68][69][70][71]. The tumour infiltrating immune cells could serve for example as an important source of angiogenetic factors [72][73][74].…”
Section: Thyroid Cancermentioning
confidence: 99%